Happiness and its relationship with locus of control and types of thinking among university students expected to graduate - Mohammad, Nasraddin E. (Humanities Journal of University of Zakho, 2024)
The current research aims to identify happiness and its relationship with the locus of control and types of thinking in terms of social and economic variables among Zakho university students expected to graduate. The sample of the research consists of (638) students selected randomly from the University. For this purpose, the researcher used four scales, the scale of happiness feeling consists of (33) items and the scale for the measurement of locus of control consists (25) items, and two scales for measuring two types of thinking: inductive and deductive thinking consist of (17) items, after extracted psychometric properties, and for the purpose of data collection appropriated statistical methods were used. The results of the study indicated that participants have happiness in general and own internal locus of control, and use both inductive and deductive thinking, and also found that there are statistically significant differences according to variables: sex, specialization, marital status, and the family's economic level, in happiness and locus of control and types of thinking among students, and also found that there is no statistically significant differences according to the other variables with the happiness among university students expected to graduate and its relationship with their locus of control and types of thinking.